A simulation of methane hydrate formation in nickel chloride solution. (15th May 2023) - Zhang, Hanmei; Li, Chang; Chen, Jun; Wu, Jianjian; Lan, Xiaobing; Liang, Zhikai; Deng, Bin
Abstract: Heavy metal is a potential threat to human, and hydrate-based method was one potential method proposed for heavy metal removal. In order to get a better understanding of the mechanism for heavy metal removal by hydrate-based method, simulation of methane (CH4 ) hydrate formation in nickel chloride (NiCl2 ) solution was conducted from molecular level by using Gromacs-2020.3 software. From the simulation results, CH4 hydrate formed in NiCl2 solution can be judged from the increasing of four-body structural order parameters (F4 ) and the decreasing of total energy. Hydrate or interfacial hydrate rather than ice was the main solid structure via CHILL + Algorithm analysis. All nickel chloride was repelled out of CH4 hydrate during 2000 ns of simulation, which corresponded with the salt-removing effect. The simulation results also indicated that chloride ion accelerated the nucleation of CH4 hydrate no matter the cation was Na + or Ni 2+ . Finally, CH4 hydrate with both Structure I (sI) and Structure II (sII) were formed in NiCl2 solution in 2000 ns of simulation, and sI type hydrate was the main CH4 hydrate structure in NiCl2 solution.